Compartmentation of Metabolites in Regulating Epigenomes of Cancer - Zhiqiang Zhao; Li Wang; Li-jun Di (BMC, 2016)
Abstract Covalent modifications of DNA and histones are important epigenetic events and the genomewide reshaping of epigenetic markers is common in cancer. Epigenetic markers are produced by enzymatic reactions, and some of these reactions require the presence of metabolites, specifically Epigenetic Enzyme Required Metabolites (EERMs), as cofactors. Recent studies found that the abundance of these EERMs correlates with epigenetic enzyme activities. Also, the subcellular compartmentation, especially the nuclear localization of these EERMs, may play a role in regulating the activities of epigenetic enzymes. Moreover, gene-specific recruitment of enzymes that produce the EERMs in the proximity of the epigenetic modification events accompanying the regulation of gene expression, were proposed. Therefore, it is important to summarize findings of EERMs in regulating epigenetic modifications at both the DNA and histone levels, and to understand how EERMs contribute to cancer development by addressing their global versus local distribution.